Letter from H. R. Linderman to James Curtis Booth, June 19, 1877 - Linderman, H. R. (Henry Richard) (1877)
Henry Richard Linderman (1825-1879), superintendent of the United States Mint, writes to James Curtis Booth (1810-1888) concerning aid extended to the manufacturer of American Refining Pots.
Keywords: Booth, James Curtis, 1810-1888; Linderman, H. R. (Henry Richard), 1825-1879; United States Mint; Mint of the United States; United States. Department of the Treasury